Prevalence and Correlates of Family Meals among Families of 3rd Graders - Susan L Davies; Kathleen F Harrington; Kevin Fontaine; Richard M Shewchuk; Michael Windle; Frank A Franklin (Archives of Community Medicine and Public Health - Peertechz Publications, 2015)
Introduction: Dietary intake has a significant role in promoting health and preventing disease. Family meals have been associated with higher nutrient intake, lower obesity rates, and other social benefits, yet little is known about what influences family meal frequency. Methods: We examined psychosocial and demographic factors potentially related to eating dinner together among families of third graders (N=1474) participating in "Hi5+," a family- and schoolbased nutrition program. Families were recruited from 33 schools to participate in a randomized trial to evaluate the efficacy of a fruit and vegetable promotion program. Results: Hierarchical sequential multiple regression identified nine independent variables that contributed significantly to predicting the frequency of family dinners. Meal-planning capability was the strongest  predictor, followed by an increased number of children in the household, lower income bracket, being White, and mothers who are not externally employed, want the family to eat together, monitor their child's intake, strongly encourage fruit and vegetable intake, and are satisfied with their family's current fruit and vegetable intake. Conclusions: Given the importance of diet in preventing obesity and many of the leading causes of death, the importance of the family in shaping future health behaviors among youth, and the influence of family practice physicians in encouraging and reinforcing caregiver behaviors, physician efforts to encourage meal planning and support family meals among their patients are warranted. These findings can have important implications for efforts to intervene before the shift to adolescence where both family meals and vegetable intake become less frequent.